(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the Histopathological pattern of Endomyometrium in atypical uterine bleeding (AUB), also to study organic causes of AUB. Study Design: A prospective, descriptive study Place and Duration of Study: This study was conducted at the Departments of Pathology and Gynaecology and Obstetrics, Bolan Medical College Complex Hospital Quetta from January 2011 to January 2013. Materials and Methods: Specimens were received as endometrial curettage and hysterectomy specimens from patients hospitalized in the dept. of Gynaecology and Obstetrics of BMC Complex Hospital Quetta. This study included 300 women’s presenting with AUB, irrespective of age and parity. A detailed clinical history followed by physical examination was also carried out in each patients to exclude systemic causes like psychological upsets and early pregnancy states and also exclude general physical abnormalities. After grossing and H&E staining all the sections were studied by group of pathologists. Results: A Total 300 cases were studied, including 100 endometrial curetting’s and 200 uteri in patients of atypical uterine bleeding at Bolan Medical Complex Hospital Quetta. The ages of these patients ranged from 20-69 years. Maximum numbers of cases were in age groups 40-49 years. Chronic endometritis (7 out of 100) 7% and the cystic hyperplasia (9 out of 100) 9% were the most important causes of atypical uterine bleeding in endometrial curetting’s. No case of endometrial carcinoma was diagnosed in this series. The histological study of hysterectomy specimen revealed multiple leiomyoma’s (135 out of 200) 67.5% and adenomyosis (38 out of 200) 19% as the commonest causes of atypical uterine bleeding. (2 out of 200) 1% case of leiomyosarcoma and (1 out of 200) 0.5% case of choriocarcinoma were diagnosed suggesting a lower frequency of uterine malignancy in our study. Conclusion: In conclusion leiomyoma’s and adenomyosis are most important causes of AUB after 3rd decade of life. Fortunately the frequency of uterine malignancy (excluding cervix) including endometrial carcinoma is much low in our setup as compared to western studies..